2008
DOI: 10.1097/hjh.0b013e3282f56bb7
|View full text |Cite|
|
Sign up to set email alerts
|

Reactive oxygen species mediate oxidized low-density lipoprotein-induced endothelin-1 gene expression via extracellular signal-regulated kinase in vascular endothelial cells

Abstract: Collectively, our data favor the notion that oxLDL stimulates ERK phosphorylation via ROS accumulation, which in turn stimulates vascular endothelial transcriptional factor activator protein-1 and ET-1 expression as well as secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 33 publications
(45 reference statements)
3
22
0
Order By: Relevance
“…It was demonstrated that a significant amount of ROS was produced spontaneously from ox-LDL at clinically relevant concentrations, and was involved in the action of ox-LDL on human umbilical vein endothelial cells [28,29], bone marrow (BM) stem cells [30], vascular smooth muscle cells [31], monocytes [32], macrophage [33] and foam cells [34]. Treatment with ox-LDL increased intracellular ROS generation in cultured endothelial cells [35].…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that a significant amount of ROS was produced spontaneously from ox-LDL at clinically relevant concentrations, and was involved in the action of ox-LDL on human umbilical vein endothelial cells [28,29], bone marrow (BM) stem cells [30], vascular smooth muscle cells [31], monocytes [32], macrophage [33] and foam cells [34]. Treatment with ox-LDL increased intracellular ROS generation in cultured endothelial cells [35].…”
Section: Introductionmentioning
confidence: 99%
“…No doubt antiinfl ammatory actions of resveratrol in this event should be able to delay or prevent endothelial dysfunctions induced by LPC. ERK, a subfamily of the mitogen-activated protein kinases (MAPK), has been reported that its activation induced by LPC in the endothelium plays a key role in evoking infl ammation and potentiating vessel contractive responses (Bochkov et al, 2002;Xu et al, 2008;Suenaga and Kamata, 2003;Matsumoto et al, 2006). In the present study, PD 98059 exerted signifi cant vasculoprotection by suppressing the local induction of infl ammatory genes and reversing LPC-induced vasoconstriction, further confi rming that ERK-activation was associated with LPC-induced endothelial dysfunction in this preparation, and elucidating a possible link between endothelial infl ammation and loss of EDR.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, NAD(P)H oxidase pathway, dysfunction of endothelium, and vascular remodeling can be the result of an activated extracellular signalā€“regulated kinases (ERK) signaling pathway. Numerous studies have shown that increased level of oxLDL induces accumulation of ROS, which stimulates ERK phosphorylation, upregulates the expression of endothelial transcriptional factor APā€1 and ETā€1, and, consequently, promotes the progression of atherosclerosis …”
Section: Redox Signaling In the Vascular Pathophysiologymentioning
confidence: 99%